Commerce et logiques d’acteurs dans la région de Kolda au Sénégal - Néné Dia (EchoGéo)
The trade of milk gradually developed in the Kolda region due to the existence of dairy belts and of a dairy basin around Kolda. The organization and the dynamics of these spaces of milk collection reveal the actors strategies. The mini-dairies’s managers and the manifold centers of the dairy basin are developing strategies of collection and marketing which vary from a space to another according to financial means and logistic. hese strategies also reveal the difficulties of the actors.